PRESERVATION OF LANGUAGE AND PRINCIPLES OF LOCAL CULTURE BASED MULTICULTURAL EDUCATION IN INDONESIA - Lina Siti Nurwahidah (Journal Of Educational Experts (JEE), 2019)
In the Orde Baru’s period, we have been directed to uniformity in many ways. Indonesia, a diverse cultural country was only directed to uniformity that would shape national culture, including Indonesian.Local diversities were just a complement, an addition to the main culture, so it was out of favor and only considered as a secondary culture. Moreover, the early '90s echoes of globalization began to enter into the soul of Indonesian society. Because ofthat, some communities in Indonesia were eroded in sense of nationalism that destabilize the use of Indonesian and glorifies all which came from abroad, including foreign languages. Whereas local culture is very important in the education of multiculturalism,it should be considered in a multicultural-region like ours, Indonesia. The reason is with the locality they can see themselves and also be able to see everyone else.Decentralization of culture including the use of regional languages will not only grow the local culture but also will raise the creativity and resilience of this nation from the onslaught of globalization.